High temperature O2 vibrational CARS thermometry applied to a turbulent oxy‐fuel combustion process. (3rd June 2016) - Tröger, Johannes W.; Meißner, Christian; Seeger, Thomas
Abstract : An O2 vibrational coherent anti‐Stokes Raman scattering system for the temperature analysis of industrially relevant staged oxy‐fuel jet burners with a thermal load of 400 kW is presented. The equivalence ratio for both investigated burners was set to ϕ = 0.9 using a mixture of pure oxygen and natural gas H (high calorific value). Temperature profiles were achieved in the mixing region of the turbulent diffusion type burners at a selected downstream position. Temperature distributions and scatter plots show local temperature variations between 447 and 3085 K and demonstrate the turbulent behavior of the combustion process. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : An O2 vibrational coherent anti‐Stokes Raman scattering system for the temperature analysis of industrially relevant staged oxy‐fuel jet burners with a thermal load of 400 kW is presented. The equivalence ratio for both investigated burners was set to ϕ =0.9 using a mixture of pure oxygen and natural gas H (high calorific value). Temperature profiles were achieved in the mixing region of the turbulent diffusion type burners at a selected downstream position.